Effect of Breastfeeding Education Program and Nurse-led Breastfeeding Online Counseling System (BMUM) for Mothers: A Randomized Controlled Study - Şimsek-Çetinkaya, Şahika; Gümüş Çaliş, Gülçin; Kibris, Şerife (SAGE Publications, 2023)
Background: Breastfeeding is very important for maternal and infant health. With first pregnancies, many pregnant people face obstacles to achieving their breastfeeding goals. Research Aims: We aimed to investigate the outcomes of a breastfeeding education program and nurse-led online breastfeeding counseling system (BMUM) on breastfeeding self-efficacy, attitudes about breastfeeding, breastfeeding problems, breastfeeding frequencies and postpartum depression. Methods: This study was a randomized controlled trial. Participants were randomly assigned to the intervention group ( n  = 36), or control group ( n  = 36). Assessments were conducted during pregnancy, between 32- and 37-weeks gestation, and on postpartum Day 1, Week 1, Week 3, and 6 months. Results: The means of the Breastfeeding Self-Efficacy–Short Form scores, and the Infant Feeding Attitude Scale (IIFAS) scores were similar between the groups at the first assessment ( p  = 0.733). IIFAS scores in the intervention group were significantly higher in the follow-up measurements on postpartum Day 1, Week 1, Week 3, and 6 months compared to scores in the control group ( p  = 0.006; p  = 0.000; p  = 0.002; p  = 0.001) Edinburgh Postpartum Depression Scale (EPDS) scores were similar between the two groups at 1 week ( p  = 0.678). EPDS scores were significantly higher in the control group on Day 1 and at 3 and 6 months postpartum ( p  = 0.000; p  = 0.038; p  = 0.042). There was no statistically significant difference in breastfeeding problems between the two groups ( p  > 0.05 across breastfeeding problems examined). The mean values of breastfeeding frequency were similar between groups on Day 1, and significantly higher in the intervention group on follow-up measurements. Conclusion: The results of this intervention appear to promote positive attitudes toward breastfeeding and decrease feelings of postpartum depression. However, further randomized controlled trials are needed to support our outcomes.
Keywords: Depression, Postpartum; Counseling; Breast Feeding; Pregnancy; Postpartum Period; Infant; Humans; Mothers; Female; Nurse's Role; Randomized Controlled Trials as Topic; 2. Zero hunger; 3. Good health